The EU's socio-economic development against the backdrop of the war in Ukraine - Kateryna Boichenko; Rana Umair Ashraf; Mário Nuno Mata; Ștefan Cristian Gherghina (Central European Economic Journal (CEEJ), 2023)
The war in Ukraine affects the European Union (EU) member states asymmetrically. The purpose of the study is to determine changes in the development of the EU countries in three key directions: 'economy and environment', 'business and trade', and 'people and work'; to identify clusters of countries with similar transformations; and to model the impact of the studied indicators on the level of public debt amid the war in Ukraine. The research methodology includes the definition of a complex indicator of changes in the socio-economic development of EU countries, correlation and cluster analysis, and modelling the influence of the studied factors/indicators on the level of public debt. Research of changes in the context of the proposed complex indicators and their components under conditions of war showed that the changes in the areas under review varied for EU countries. Against the backdrop of the war in Ukraine, 17 EU countries faced a slowdown in their socio-economic growth, among which Poland was the most severely affected. Modelling made it possible to determine that, amid the war, the most important factors for the EU public debt are inflation, labour market conditions, and the possibilities of the balance of payments and the international investment position incorporated into GDP. The conducted research proves that the war in Ukraine increases the scale and relevance of general challenges that cannot be addressed at the national level. Strengthening the European defence against external aggression is the entire task of the EU.
Keywords: O11; O52; 330; development; public debt; inflation; clustering; war